A Study of Deep Belief Network Based Chinese Speech Emotion Recognition - Bu Chen; Qian Yin; Ping Guo (2014 Tenth International Conference on Computational Intelligence and Security, 2014)
This paper presents a deep learning method application to the extraction of emotions included in Chinese speech with a deep belief network (DBN) structure. Eight proper features such as pitch, mel frequency cepstrum coefficient (MFCC) are chosen from Mandarin speech used as network inputs, and a DBN classifier is used instead of traditional shallow learning methods to recognition of emotions. Experiment studies have proven that its recognition rate is higher than that of the traditional back propagation (BP) method and support vector machine (SVM) classifier.